TREATMENT OF HBV AND HDV CO-INFECTION USING LAMIVUDINE - Qureshi, Huma; Arif, Ambreen; Alam, Ejaz (Journal of Ayub Medical College Abbottabad, 2009)
Objective: To see effect of Lamivudine on sero conversion of HBeAg positive cases co infected with Delta hepatitis. Methods: Hepatitis B positive patients with deranged liver functions for 6 months were tested for HBeAg, HBV DNA and anti-Delta virus (HDV), using ELISA. Patients were divided into 2 groups, group 1: HBeAg, HBV DNA positive (wild type) but delta negative and group 2: HBeAg, HBV DNA positive (wild type) with delta positive. Lamivudine (100 mg) was advised to both groups till sero-conversion. Results: Of 124 cases in year 1999-2005, 69 were in (Group 1), and 55 were in (Group 2). Eighty percent were males in both groups. ALT normalisation occurred in 75%, 24% cases within 6 months respectively. At the start of therapy mean HBeAg was 289±189 in group 1 and 142±160 in group 2. With treatment, the values did not change much till 12 months of therapy. The fall was significantly slow in delta positive cases. At 36 months 26 (38%) cases in group 1 and 9 (16.4%) cases in group 2 sero-converted. Nine cases in each group remained non-responders while 2 in each group relapsed. Conclusion: Wild type of HBV/HDV co-infected cases have a 16% chance of seroconversion which negates the concept that once infected with delta virus there is not much that can be done. Keywords: Hepatitis B virus, Delta hepatitis, co-infection, sero-conversion, fulminant hepatitis, lamuvidine, interferon, entecavir